Implementation of Smart Feeder Based on Internet of Things (IoT) for Fish Aquarium - Misniati, Misniati; Delsi Samsumar, Lalu; Zaenudin, Zaenudin (Ali Institute of Research and Publication, 2026)
Household aquarium maintenance is generally performed manually, including feeding, monitoring temperature and turbidity, and water replacement, which is time-consuming and may reduce water quality, leading to stress or fish mortality. Although Internet of Things (IoT) technology has developed, its application in household aquariums remains limited. This study designed and implemented an IoT-based smart feeder with automatic feeding, water quality monitoring, and automatic water replacement using ESP32, DS18B20 temperature sensor, turbidity sensor, ultrasonic sensor, RTC, servo motor, water pump, and the Blynk application, applying a prototyping method. Tests showed the DS18B20 sensor had an average error of ±1.55% with 98.45% accuracy and ±1.5 s response time; the turbidity sensor distinguished clear and turbid conditions with 99% accuracy and ±2 s response; the ultrasonic sensor reached 92%; feed distribution achieved 98.6% with 1.2 s servo response; and water replacement achieved 66.7%–90% depending on turbidity threshold, with Blynk latency <2 s. Overall, the system achieved an average success rate of 91.5%, reducing manual workload, maintaining optimal water quality, and improving user convenience, while providing opportunities for further IoTbased aquarium automation development at the household scale